Learning Transfer: The Missing Link to Learning among School Leaders in Burkina Faso and Ghana - Brion, Corinne; Cordeiro, Paula A. (Frontiers in Education, 2018)
Every year billions of dollars are spent on development aid and training around the world. However, only 10% of this training results in the transfer of knowledge, skills, or behaviors learned in the training to the work place. Ideally, learning transfer produces effective and continued application by learners of the knowledge and skills they gained through their learning activities. Currently, there is a limited body of research examining the factors that hinder and promote learning transfer in professional development, particularly the professional development of school leaders in developing countries. This qualitative exploratory study sought to address the gap in the literature by examining 6 schools: 3 in Burkina Faso and 3 in Ghana, West Africa. This investigation explored what promoted and hindered learning transfer in both countries. The sample consisted of 13 West African school leaders (6 in Burkina Faso and 7 in Ghana) who attended a three-day leadership training workshop. Data collection included in-depth interviews, document analysis, post-training site visits, and text messages to ascertain whether this mobile technology intervention enhanced learning transfer. The findings demonstrated that learning transfer occurred in both countries in all six schools. Data indicated that most of the transfer of learning happened in areas not requiring mindset and behavioral changes. Data suggested that the facilities in which the trainings took place, the facilitators’ dispositions and knowledge, the adequacy of the materials as well as the testimonials and certificate of completions enhanced the transfer of learning. Participants also indicated some inhibitors to the transfer of learning, such as financial, cultural, and human behavior constraints. This study helps increase our understanding of what promotes and inhibits learning transfer in educational settings in Burkina Faso and Ghana and provides suggestions for trainers and teachers who facilitate trainings.